Biowaste-derived carbon black applied to polyaniline-based high-performance supercapacitor microelectrodes: Sustainable materials for renewable energy applications - Goswami, Sumita (2020)
Biowaste, derived from cooking-oven-produced carbon nanoparticles (WCP), are incorporated into polyaniline (PANI) via in-situ chemical oxidative polymerization to achieve excellent electrochemical properties for application in supercapacitors. The WCP-PANI composite electrodes have shown high-performance charge storage, due to combinatorial effect of electrical double layer capacitance from WCP and pseudocapacitance from PANI. With increase in the WCP percolation, work function of PANI is increased, which improves the charge-trapping capabilities of composites. For such distinct charge-trapping mechanism, areal capacitance of the composite microelectrode remains near-constant with increase in scan rate or current density. This indicates the suppression of diffusion limitations at higher scan rates to considerably enhance the rate capability. Also, with increasing polymerization time, strong interaction in this conjugated system greatly improves the charge-transfer reaction between PANI and WCP. The areal capacitance of the composite electrode is found to increase more than 600 times over pure PANI electrode. Moreover, energy-power performance of the microelectrode reveals almost 550% increment in the power density with a mere 1% decrement in energy density. Such rationally synthesized WCP-PANI composite electrodes using biowaste carbon nanomaterials, provide opportunities for the development of next-generation green-supercapacitors with improved energy storage performance.